UJI EFEK ANTIDIARE EKSTRAK ETANOL KULIT BUAH PISANG AMBON (Musa acuminata Colla) TERHADAP MENCIT JANTAN (Mus Musculus L.) YANG DIINDUKSI MINYAK JARAK (Oleum Ricini) - Serang, Yithro; Wijayanti, Maria Widya Riska (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2022)
Utilization of plants as a treatment for diarrhea is an alternative to traditional medicine. Ambon banana peel is one of the plants that can be used as an antidiarrheal because it contains flavonoid compounds, tannins and saponins. This study aimed to determine the antidiarrheal effect of the ethanol extract of Ambon banana peel on male mice induced by Oleum Ricini and to determine the dose of ethanol extract of Ambon banana peel that gave the best antidiarrheal effect. Ambon banana peel was extracted by maceration method. The research method used was a laboratory experimental study using 25 male mice which were divided into 5 groups, namely the negative control group (given CMC Na 1%), the positive control group (given Loperamide HCl 2 mg), the treatment group with ethanol extract of Ambon banana peel. with varying doses of 300 mg/KgBW, 600 mg/KgBW and 900 mg/KgBW. The antidiarrheal effect was observed every 30 minutes for 4 hours with the parameters used were diarrhea frequency, stool weight and stool consistency. Based on the results of the study, the ethanol extract of Ambon banana peel at a dose of 900 mg/KgBW showed diarrhea frequency and stool weight results which were almost the same as the Loperamide HCl treatment group. The results of statistical analysis using ANOVA obtained p<0.05, this indicates that there is a significant difference. The ethanol extract of Ambon banana peel at a dose of 900 mg/KgBW had the best antidiarrheal effect compared to the ethanolic extract of Ambon banana peel at a dose of 300 mg/KgBW and a dose of 600 mg/KgBW.